2019
DOI: 10.1002/ijgo.12998
|View full text |Cite
|
Sign up to set email alerts
|

Use of an antiemetic to shorten the length of labor in nulliparous women, exploring a potential role of an old drug: A randomized controlled trial

Abstract: Objective To assess whether metoclopramide is effective in shortening the duration of the first stage of labor in primiparous women. Methods The present randomized, double‐blind, placebo‐controlled trial was conducted at King Faisal Hospital, Saudi Arabia (between July 30, 2013, and September 1, 2016), and sequentially recruited young nulliparous women admitted in spontaneous active labor with or without ruptured membranes. Eligible participants were randomly assigned to receive a slow intravenous injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The results agree with study [5] by Ellaithy etal., 2019, also there were no statistically significant differences between both groups regarding labor pain using VAS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results agree with study [5] by Ellaithy etal., 2019, also there were no statistically significant differences between both groups regarding labor pain using VAS.…”
Section: Discussionsupporting
confidence: 93%
“…The sample size was determined according to the primary outcome variable which was the cervical dilation rate. According to the literature [5] , it was reported that the cervical dilatation rate was (2.4 ± 0.4 cm/hr among those who received metoclopramide versus 1.9 ± 0.5 cm/h in the placebo group, P<0.001).…”
Section: Sample Size Calculationsmentioning
confidence: 99%